China`s demographic onus and its implications for The Japan-U.S. Alliance: the increasing need for Deterring China`s Aggression against The Senkaku Islands - Matsumura, Masahiro (Penerbit UKM, 2014)
This paper will focus on the “demographic onus effect” to challenge established cognitions of rising China. The country’s demographic dynamics, especially the trade-off between a military build-up and welfare spending, will most probably lead to what might be called a “geriatric peace” by around 2030. This is because, due to its long-time one child policy, China is set to confront an unprecedented ageing population before becoming an advanced industrial country. Until then, however, the Chinese will have the fiscal wherewithal to continue the country’s formidable military accrual. China is also likely to become far more belligerent by manipulating nationalist sentiments at home, alongside using foreign policy to divert growing popular discontent. This paper will analyze China’s demographic dynamics and explore the implications of the ageing population to Japan’s security, with the focus on a possible contingency over the Senkaku Islands as the most likely flash point. It will conclude with policy recommendations for Japan and the U.S. to weather possible China’s bellicosity during the next ten to fifteen years.